Perancangan dan Evaluasi UI/UX Website Pemesanan Menu Berbasis Design Thinking Menggunakan Instrumen User Experience Questionnaire (UEQ) - Tasya Suboong; Nur Widjiyati (Applied Information Technology and Computer Science (AICOMS), 2026)
The menu ordering process at Warung Makan Mbak Lutfi is currently still carried out conventionally, which often leads to recording errors and customer queue accumulation. This study aims to design and evaluate a menu ordering website interface capable of improving operational efficiency and user experience. The methodology applied in this research is Design Thinking, which includes the stages of empathize, define, ideate, prototype, and testing. The interface quality evaluation was conducted using the User Experience Questionnaire (UEQ) involving 36 respondents. The results indicate that the website-based design successfully facilitates both online and offline user needs in monitoring menu stock availability. Based on the UEQ testing results, the system achieved high scores across all scales, namely Attractiveness (2.04), Perspicuity (2.19), Efficiency (2.10), Dependability (1.87), Stimulation (2.08), and Novelty (1.85), all of which fall into the “Excellent” category. It can be concluded that the implementation of the Design Thinking method produced an intuitive and innovative digital solution capable of delivering a highly satisfying user experience according to UEQ benchmark standards.